Kirschner wire placement in scaphoid bones using intraoperative CT-guided stereotaxy. Issue 3 (June 2013) - Niederwanger, Christian; Widmann, Gerlig; Knoflach, Martin; Schullian, Peter; Hoermann, Romed; Bale, Reto
Abstract Background: Minimally invasive ostesynthesis of scaphoid fractures may reduce the risk of fracture non-union and shorten the duration of illness. The aim of this study was to analyze the technical feasibility and targeting accuracy of computed tomography (CT) – guided stereotactic Kirschner (K)-wire positioning in the scaphoid. Methods: Nineteen Formalin preserved cadaveric upper extremities (10 right, 9 left) were fixed in 90 degree dorsal extension for percutaneous access from palmar. An ideal central position of the K-wire was planned on the computer adapted from intraoperative CT data. A 3D navigation system and stereotactic targeting device were used for K-wire placement. Target positioning errors were evaluated by fusion of the control CT with the K-wire in place with the planning CT. Results: The procedure allowed for an easy and rigid wrist fixation. K-wire placement showed mean ± SD lateral targeting errors of 0.9 ± 0.5 mm at the scaphoid bone entry and 1.2 ± 0.7 mm at the K-wire tip. The mean angular error was 1.3° ± 1.1° . Total duration of the intervention ranged between 19 and 23 min. Conclusion: CT-guided stereotactic K-wire placement in scaphoid bones is highly accurate. The technique may guide minimally invasive screw-osteosynthesis of scaphoid fractures.